If all acts of love and pleasure are Her rituals, what about BDSM? Feminist culture wars in contemporary Paganism. Issue 1 (2nd January 2018) - Mueller, Michelle
ABSTRACT: Since the 1970s, some religious practitioners of the contemporary Pagan movement (a.k.a. Neo-Paganism) have embraced spiritual BDSM, or "sacred kink, " as a spiritual discipline relating to their tradition. The "sex wars, " debates around pornography, prostitution, and sadomasochism, have appeared in the history of Wicca and contemporary Paganism. Pagan feminists have brought theological questions to the same debates. They have focused on the Wiccan Rede ("harm none") and the affirmation of pleasure in Doreen Valiente's Charge of the Goddess that states that, "All acts of pleasure are [the Goddess's] rituals." While support for BDSM has become the dominant public perspective in twenty-first-century Paganism, the movement's late twentieth-century history includes instances of anguish as individuals wrestled with their personal sexual desire and their feminist principles.